2022
DOI: 10.3390/ijerph19138192
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education with Eduball Stimulates Non-Native Language Learning in Primary School Students

Abstract: Although the neuronal mechanisms of action and cognition are related, the division of intellectual and physical lessons is standard in schools. This is surprising, because numerous studies show that integrating physical education (PE) with teaching content stimulates critical skills. For example, several experiments indicate that Eduball-based PE (i.e., lessons in a sports hall during which students play team mini-games with educational balls with printed letters, numbers, and other signs) develops mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…We found that a minimum of 24 participants are required, with 12 in each group (with an expected large effect size). Inclusion and exclusion criteria were the same as in our earlier studies (e.g., [ 27 ]). In short, inclusion criteria were as follows: being a learner of the selected class and frequently participating in activities during the investigational period, while exclusion criteria were as follows: contraindications for participation in PE and omitted pre-test or/and post-test.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that a minimum of 24 participants are required, with 12 in each group (with an expected large effect size). Inclusion and exclusion criteria were the same as in our earlier studies (e.g., [ 27 ]). In short, inclusion criteria were as follows: being a learner of the selected class and frequently participating in activities during the investigational period, while exclusion criteria were as follows: contraindications for participation in PE and omitted pre-test or/and post-test.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining class ensured the implementation of the formal requirements of the curriculum. As in the Eduball experiments replicated here [ 24 , 25 , 26 , 27 , 31 , 59 , 60 , 61 ], various activities from the Eduball games set [ 65 , 66 ] were integrated with PE lesson plans. The games were chosen in compliance with the curricula and the day’s theme.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations